GLI1 Inhibitor SRI-38832 Attenuates Chemotherapeutic Resistance by Downregulating NBS1 Transcription in BRAFV600E Colorectal Cancer - Zhang, Ruowen; Ma, Jinlu; Avery, Justin T.; Sambandam, Vijaya; Nguyen, Theresa H.; Xu, Bo; Suto, Mark J.; Boohaker, Rebecca J. (Frontiers in Oncology, 2020)
Resistance to radiation and chemotherapy in colorectal cancer (CRC) patients contribute significantly to refractory disease and disease progression. Herein, we provide mechanistic rationale for acquired or inherent chemotherapeutic resistance to the anti-tumor effects of 5-fluorouracil (5-FU) that is linked to oncogenic GLI1 transcription activity and NBS1 overexpression. Patients with high levels of GLI1 also expressed high levels of NBS1. Non-canonical activation of GLI1 is driven through oncogenic pathways in CRC, like the BRAFV600E mutation. GLI1 was identified as a novel regulator of NBS1 and discovered that by knocking down GLI1 levels in vitro, diminished NBS1 expression, increased DNA damage/apoptosis, and re-sensitization of 5-FU resistant cancer to treatment was observed. Furthermore, a novel GLI1 inhibitor, SRI-38832, which exhibited pharmacokinetic properties suitable for in vivo testing, was identified. GLI1 inhibition in a murine BRAFV600E variant xenograft model of CRC resulted in the same down-regulation of NBS1 observed in vitro as well as significant reduction of tumor growth/burden. GLI1 inhibition could therefore be a therapeutic option for 5-FU resistant and BRAFV600E variant CRC patients